2013
DOI: 10.4236/jwarp.2013.511111
|View full text |Cite
|
Sign up to set email alerts
|

Ion Exchange Equilibrium between DOWEX 1X8 Resin Modified by Polyethyleneimine and Electrolyte Solutions

Abstract: In order to improve the selectivity of anion exchange resin, the surface of gel type anion exchange resin was modified with polyethyleneimine (PEI). In the proposed work an attempt to the utilization of commercial anion exchange resin modified by adsorption of polyethyleneimine was investigated. Many conditions of modification of anion exchange resin surface were studied. The influent parameters on the DOWEX 1X8 resin modification were determined using a factorial experimental design. The ion exchange reaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 28 publications
(29 reference statements)
1
4
0
Order By: Relevance
“…These results are in agreement with several studies, [21,22,30] using either anion exchange membrane or resin. Sata et al [30] proved that the modification of the anionic membrane surface by polyethyleneimine makes the membrane more selective for nitrate than chloride and sulphate ions.…”
Section: Effect Of Surface Modification On Adsorptive Membrane Selectsupporting
confidence: 94%
See 4 more Smart Citations
“…These results are in agreement with several studies, [21,22,30] using either anion exchange membrane or resin. Sata et al [30] proved that the modification of the anionic membrane surface by polyethyleneimine makes the membrane more selective for nitrate than chloride and sulphate ions.…”
Section: Effect Of Surface Modification On Adsorptive Membrane Selectsupporting
confidence: 94%
“…Hannachi et al studied the ion exchange equilibrium between Dowex 1 × 8 resin modified by PEI and electrolyte solutions. They found that the modified resin has a greater affinity for monovalent anions.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations